2018
DOI: 10.1002/bjs.10729
|View full text |Cite
|
Sign up to set email alerts
|

Using textbook outcome as a measure of quality of care in oesophagogastric cancer surgery

Abstract: Textbook outcome is a clinically relevant measure in patients undergoing oesophagogastric cancer surgery as it can identify underperforming parameters in a hospital setting. Overall survival in patients with a textbook outcome is better than in patients without a textbook outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 38 publications
5
78
0
1
Order By: Relevance
“…The multidimensional parameter TO is a relatively new concept which was found useful in other fields of surgery. [13][14][15]17,18 Our definition of TO was established by an international survey, conducted among experts in quality improvement in (pancreatic) surgery. Out of 17 items, absence of 6 complications was considered to reflect the ideal outcome after pancreatic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multidimensional parameter TO is a relatively new concept which was found useful in other fields of surgery. [13][14][15]17,18 Our definition of TO was established by an international survey, conducted among experts in quality improvement in (pancreatic) surgery. Out of 17 items, absence of 6 complications was considered to reflect the ideal outcome after pancreatic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…16 Nevertheless, previous studies in other surgical fields demonstrated that TO was a feasible and useful parameter for comparison of quality between institutions, also showing correlation with improved long-term outcomes after cancer surgery. [13][14][15]17,18 This study proposes a TO definition for pancreatic surgery, based on the opinion of international experts, and assesses predictors and associations with TO in a nationwide surgical audit.…”
mentioning
confidence: 99%
“…Using consensus amongst surgeons from the USSC high volume institutions based on previously published criteria, 7,20,21,23,25…”
Section: Textbook Outcomementioning
confidence: 99%
“…While there is no standardized definition that has been reached in the literature, the definition was adapted based on previously published studies and available cohort characteristics. 7,20,21,23,25 Notably, this definition does not include important patientreported outcomes such as patient satisfaction and quality of life, which have been previously demonstrated to correlate with the quality of care. [49][50][51] Future studies should employ stakeholders beyond the surgeon as well as prospective data to develop and validate consensus TO definitions.…”
Section: Long-term Impact Of Textbook Outcomementioning
confidence: 99%
See 1 more Smart Citation